Kondisi Sosial Ekonomi Keluarga Petani Padi di Desa Kresnowidodo Tahun 2018 - Supatmiatun Supatmiatun; Yarmaidi Yarmaidi; Nani Suwarni (JPG (Jurnal Penelitian Geografi), 2019)
The purpose of this research was to find out information about social economic condition of rice farming in the Kresnowidodo village at 2018. This research used descriptive method. The total population is 617 head of rice farming families, data was taken 10% (62 KK). The data were collected through observation techniques, interviews, questionnaires, and documentation. The data were analyzed by using presentage descriptive. The result of the research showed: 1) most of rice farmers have narrow rice field (0.5 ha). 2) Most of rice farmers did not manage their rice field. 3) Most of rice farmers have an income below the average. (IDR.14,532,000,-) 4) Most of rice farmers have job outside of agriculture’s job as laborers, contruction workers, rice mills, wood craftsman, and trader. 5) The average children of rice farmers took basic education level. 6) The average poverty level of rice farmers were in the category of almost poor.Tujuan penelitian ini untuk mengetahui informasi tentang kondisi sosial ekonomi keluarga petani padi di Desa Kresnowidodo tahun 2018. Penelitian ini menggunakan metode deskriptif. Jumlah populasi adalah 617 kepala keluarga petani padi, sampel diambil 10% (62 KK). Data dukumpulkan melalui observasi, wawancara, kuesioner, dan dokumentasi. Data dianalisis dengan menggunakan deskriptif persentase. Hasil penelitian menunjukkan: 1) sebagian besar petani padi memiliki lahan sempit (0,5 ha). 2) Sebagian besar petani padi tidak mengelola lahannya setelah panen. 3) Sebagian besar petani padi memperoleh pendapatan di bawah rata-rata (Rp.14.352.000,-). 4) Sebagian besar petani padi memiliki pekerjaan di luar usaha tani sebagai buruh, kuli bangunan, penggiling padi, pengrajin kayu dan pedagang. 5) Rata-rata anak dari petani padi menempuh tingkat pendidikan dasar. 6) Rata-rata tingkat kemiskinan petani padi berada pada kategori nyaris miskin.Kata kunci: ekonomi, petani padi, sosial